Education and the Timing of Family Formation: Evidence from Quantile Regression Analysis - Ewa Batyra (Development and Change, 2024)
The relationship between educational level and the age at which women start families has been extensively researched. However, studies have primarily explored how additional schooling shifts the mean or, more broadly, only one point of the age at first union and first birth distributions. This ignores variation in the association between education and the timing of family formation, and the fact that schooling might shape behaviours of vulnerable and more privileged women differently. Using quantile regressions, this article examines heterogeneity in the relationship between education and the age at first union and first birth across the distribution of these events within 50 low- and middle-income countries. It investigates whether additional schooling shifts relatively early union formation and childbearing (that is, lower parts of distributions) similarly or differently than it shifts other parts of the distributions. It finds that association between an additional year at school and the age at first union and birth is weaker in the lower than the upper parts of the distributions. Education has a relatively weak effect on the reduction of early first unions and births and plays an unequalizing role in shaping family formation within countries. These findings are key to understanding persistently high levels of early marriage and pregnancy, despite the expansion of education.
Keywords: 300